Community Empowerment in Drainage Management to Overcome Floods - Ilwandri; Apriani Sijabat; Makkah HM; Andi Sri Rezky Wulandari; Andi Rahmah; Santi Mareta; Nanich Framulya (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2023)
Flooding is a serious problem that often disrupts the lives of urban communities. Increased rainfall intensity, climate change, and rapid urban development have made existing drainage systems less effective at coping with flooding. To face this challenge, this study aims to examine community empowerment efforts in drainage management as a flood mitigation strategy. This research was conducted by combining participatory approaches and field research methods. Local communities, local governments, and stakeholders are involved in planning, implementing, and evaluating empowerment programs. This program includes skills training, education on the importance of drainage maintenance, as well as the formation of community groups active in drainage maintenance. The results showed that community empowerment in drainage management has had a positive impact in reducing flood risk. Community groups involved in this program actively maintain the cleanliness and drainage function in their neighborhoods. In addition, education about climate change and rain patterns also helps people to be better prepared for extreme conditions.